Achieving Resilience: Data Loss and Recovery on Devices for Personal Use in Three Countries - Wunder, Julia; Wash, Rick; Renaud, Karen; Oliveira, Daniela A.; Benenson, Zinaida (Conference on Human Factors in Computing Systems - Proceedings, 2025)
Recovery from adverse incidents, such as accidents or cyber attacks, is a cornerstone of cyber resilience. Backups are essential in facilitating systems recovery. We have limited understanding of how devices for personal use are backed up, and of how data loss and recovery occur, including which factors might be helpful to afford resilience. To gain insights, we surveyed almost representative (in age and gender) samples of German, UK and USA populations, 1423 in total. Almost half of the participants (656, 46%) experienced at least one data loss incident. Whereas 42% of 656 participants recovered using backups, over half of them had outdated or incomplete backups. High levels of stress were reported, especially by those recovering without backups or with problematic backups. In the full sample, 86% of participants created full or partial backups of at least one of their devices, the most important trigger being prior data loss experiences.
CRIS-Team Scopus Importer:2025-05-30
Keywords: backup; desktop; laptop; mobile; recovery; resilience

Analyse verbreiteter Anwendungen zum Lesen von elektronischen Büchern - Benenson, Zinaida; Berger, Frederik; Cherepantsev, Anatoliy; Datsevich, Sergey; Do, Long; Eckert, Moritz; Elsberger, Tassilo; Freiling, Felix; Frinken, Marius; Glameyer, Hendrik; Hafner, Steffen; Hagenhoff, Svenja; et al. (2019)
Der Marktanteil elektronischer Bucher (E-Books) am Buchmarkt wächst beständig. Um E-Books zu rezipieren, benötigt man spezielle Leseumgebungen, die als Software (im Browser oder als eigene Anwendung) oder als Spezialgerät (E-Reader) realisiert sein können. Diese Leseumgebungen sind geeignet, Daten über das Leseverhalten zu sammeln. Im Rahmen einer universitären Lehrveranstaltung wurden die Software-Leseumgebungen der beiden deutschen Marktführer Kindle und Tolino untersucht. Der vorliegende Bericht fasst die Ergebnisse dieser Analysen zusammen. Das Ergebnis ist eine umfassende Bestandsaufnahme der digitalen Spuren, die durch die Benutzung der Programme entstehen. Betrachtet wurden die zum Untersuchungszeitpunkt aktuellen Versionen der jeweiligen Webanwendungen und Android-Apps sowie des Kindle-Windows-Clients. Die Ergebnisse entstanden im Rahmen einer Übung zur Vorlesung "Fortgeschrittene forensische Informatik II" im Wintersemester 2018/19 an der Friedrich-Alexander-Universität Erlangen-Nürnberg (FAU), die gemeinsam durchgeführt wurde vom Lehrstuhl fur Informatik 1 und dem Institut für Buchwissenschaft an der FAU.

From Chaos to Consistency: The Role of CSAF in Streamlining Security Advisories - Wunder, Julia; Aurich, Janik; Benenson, Zinaida (The 2024 European Symposium on Usable Security, 2024)
Security advisories have become an important part of vulnerability management. They can be used to gather and distribute valuable information about vulnerabilities. Although there is a predefined broad format for advisories, it is not really standardized. As a result, their content and form vary greatly depending on the vendor. Thus, it is cumbersome and resource-intensive for security analysts to extract the relevant information. The Common Security Advisory Format (CSAF) aims to bring security advisories into a standardized format which is intended to solve existing problems and to enable automated processing of the advisories. However, a new standard only makes sense if it can benefit users. Hence the questions arise: Do security advisories cause issues in their current state? Which of these issues is CSAF able to resolve? What is the current state of automation? To investigate these questions, we interviewed three security experts, and then conducted an online survey with 197 participants. The results show that problems exist and can often be traced back to confusing and inconsistent structures and formats. CSAF attempts to solve precisely these problems. However, our results show that CSAF is currently rarely used. Although users perceive automation as necessary to improve the processing of security advisories, many are at the same time skeptical. One of the main reasons is that systems are not yet designed for automation and a migration would require vast amounts of resources.
Keywords: CSAF; Common Security Advisory Format; Security Advisories; IT Security; Survey; User Study

On NVD Users’ Attitudes, Experiences, Hopes and Hurdles - Wunder, Julia; Corona, Alan; Hammer, Andreas; Benenson, Zinaida (Digital Threats: Research and Practice, 2024)

Shedding Light on CVSS Scoring Inconsistencies: A User-Centric Study on Evaluating Widespread Security Vulnerabilities - Wunder, Julia; Kurtz, Andreas; Eichenmüller, Christian; Gassmann, Freya; Benenson, Zinaida (2024 IEEE Symposium on Security and Privacy (SP), 2024)
The Common Vulnerability Scoring System (CVSS) is a popular method for evaluating the severity of vulnerabilities in vulnerability management. In the evaluation process, a numeric score between 0 and 10 is calculated, 10 being the most severe (critical) value. The goal of CVSS is to provide comparable scores across different evaluators. However, previous works indicate that CVSS might not reach this goal: If a vulnerability is evaluated by several analysts, their scores often differ. This raises the following questions: Are CVSS evaluations consistent? Which factors influence CVSS assessments? We systematically investigate these questions in an online survey with 196 CVSS users. We show that specific CVSS metrics are inconsistently evaluated for widespread vulnerability types, including Top 3 vulnerabilities from the "2022 CWE Top 25 Most Dangerous Software Weaknesses"list. In a follow-up survey with 59 participants, we found that for the same vulnerabilities from the main study, 68% of these users gave different severity ratings. Our study reveals that most evaluators are aware of the problematic aspects of CVSS, but they still see CVSS as a useful tool for vulnerability assessment. Finally, we discuss possible reasons for inconsistent evaluations and provide recommendations on improving the consistency of scoring.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Consistency of Evaluations; CVSS; User Study